INTELECTUAIS E EDUCAÇÃO NA DIOCESE DE GUARAPUAVA: DISCURSOS DE DOM HELMEL E DOM CAVALLIN (1965-1992) - Queirós, Janete (2012)
This dissertation analyzes the theological-political project of the Diocese of Guarapuava in the period within 1965 and 1992, particularly the pastoral actions of D. Frederick D. and Helmel Albano Bortoletto Cavallin. The analytical perspective is situated within the history of education, specifically in Intellectual History, in which the bishops are understood as intellectuals of the religious field, who support the use of religion in their community, and shall strengthen the teaching population education. Specifically, the research objectives are to reconstruct some aspects of the creation and installation of DG and discuss which educational practices the prelates developed to expand and maintain the legitimacy of the Catholic Church among the people of God, emphasizing the historical aspects that show the inclusion of DG in the organizational structure of Catholicism in Brazil, advocated by the Vatican and clergy organizations in Latin America and Brazil.The research is based on Pierre Bourdieu, particularly in the field concepts and strategy as well as in the Book Tombo, Diocesan Bulletin and newspapers from Guarapuava, which allowed us to discuss the political project of DG-pastoral, emphasizing the struggles waged in the religious field, without disregard the relations with other fields of the social world. Under the light of these concepts and the historical sources it can be argued that the installation of the diocese was a strategy of the Catholic Church to defend the Catholicism as a religion of social prestige in the social environment and ensure closer ties between clergy and the people of God. More precisely, the pastoral actions created in DG had a direct relationship with the guidelines coming from the Vatican and with the decisions taken in CNBB, although the prelates of Guarapuava have given peculiar directions to the actions undertaken in DG. Those actions of DG consisted in the creation of Diocesan Bulletin, institutional expansion, foundation of the Diocesan Seminary, Biblical Circles, investment in training of young Catholics, Catechisms and Religious Education in schools, which emphasized a view of the world more concerned with spiritual values, that is, with the Kingdom of God. However, you can also say that DG was involved, although less intense, with social problems, or problems with the world of men, particularly when making complaints and criticisms against the misery and promoting the protection and enhancement of human rights. Therefore, these postures, apparently ambiguous and contradictory, highlight the dilemmas experienced by the prelates of the DG, because they sometimes took a conservative position to defend the traditional precepts of the Catholic Church, sometimes one of progressive character, positioning themselves in defense of social justice.